2011
DOI: 10.1021/mp100356k
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Imaging of Nanovaccine Carriers Targeted to Human Dendritic Cells

Abstract: Dendritic cells (DCs) are key players in the initiation of adaptive immune responses and are currently exploited in immunotherapy against cancer and infectious diseases. The targeted delivery of nanovaccine particles (NPs) to DCs in vivo is a promising strategy to enhance immune responses. Here, targeted nanovaccine carriers were generated that allow multimodal imaging of nanocarrier-DC interactions from the subcellular to the organism level. These carriers were made of biodegradable poly(D,L-lactide-co-glycol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 40 publications
2
57
0
Order By: Relevance
“…De Vries et al have shown that in vivo magnetic resonance tracking of MNS labeled dendritic cells is feasible in humans in conjunction with detailed anatomical information in melanoma patients. In contrast to scintigraphic imaging, MRI allowed assessment of the accuracy of dendritic cell delivery and of inter- and intranodal cell migration patterns [139143]. Recently, Bulte et al evaluated the long-term clinical tracking of MNS labeled stem cells after intracerebroventricular transplantation in an 18-month-old patient with global cerebral ischemia [144].…”
Section: Mns For Diagnostic Imaging Of Cancermentioning
confidence: 99%
“…De Vries et al have shown that in vivo magnetic resonance tracking of MNS labeled dendritic cells is feasible in humans in conjunction with detailed anatomical information in melanoma patients. In contrast to scintigraphic imaging, MRI allowed assessment of the accuracy of dendritic cell delivery and of inter- and intranodal cell migration patterns [139143]. Recently, Bulte et al evaluated the long-term clinical tracking of MNS labeled stem cells after intracerebroventricular transplantation in an 18-month-old patient with global cerebral ischemia [144].…”
Section: Mns For Diagnostic Imaging Of Cancermentioning
confidence: 99%
“…17 Limited studies have explored the use of carbohydrate-functionalized vaccine carriers as targeting vehicles, with most studies using antibodies as ligands. 18 This study outlines a novel approach to target the mannose receptor (CD206) and CIRE (CD209) on murine DCs by mimicking carbohydrate moieties found on the surface of pathogens. 19 Polyanhydride nanoparticle surfaces were functionalized with dimannose in order to study specific interactions with both CLRs known to recognize mannose residues.…”
Section: Abstract: Polyanhydrides Nanoparticles Carbohydrates Dendmentioning
confidence: 99%
“…In diagnostic, prophylactic and therapeutic approaches, nanoparticles have been used for imaging purposes [9], and/or as drug carrying adjuvant to enhance virucidal properties [10]. Virucidal nanoparticles and drug delivery models have been used mainly for the fighting Human immunodeficiency virus (HIV), hepatitis (type A, B, C and E) and herpes simplex virus (HSV-1&2).…”
Section: Introductionmentioning
confidence: 99%